Comparison of Diaphragm Thickness and Excursion between Patients with Pelvic Girdle Pain and Healthy Individuals - Nassiri, Keyvan; Abedi, Mohsen; Akbarzadeh Baghban, Alireza; Heydarpour Meymeh, Maryam; Dehghan Manshadi, Farideh (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Inspiratory muscles play an important role in respiration and spinal control. Therefore, diaphragm thickness and excursion must logically be correlated to the dual action of the diaphragm. This study investigated the difference between diaphragm thickness and excursion in quiet and deep breathing between patients with pelvic girdle pain (PGP) and healthy individuals by using rehabilitative ultrasound imaging (RUSI). Materials and Methods: Images of diaphragm thickness were taken using Brightness (B) mode RUSI in the intercostal space between the 7th and 8th, or 8thand 9th ribs, and diaphragm excursion was assessed using Motion (M) mode RUSI at the right midclavicular line. Imaging was performed in 30 participants with PGP and in 30 asymptomatic women and men (control group) aged 20-48 years in both groups. Results: In individuals with PGP, the diaphragm thickness and excursion were significantly lower than the control group at end-expiration in the deep and quiet breathing. Conclusion: The PGP group showed reduced diaphragm thickness and excursion. Therefore, it seems that breathing training and exercise should be performed along with other forms of training. Keywords: Diaphragm; Thickness; Excursion; Ultrasonography; Pelvic Girdle Pain